Modelling the underpinning factors of word of mouth (WOM) intentions of students in an ODL institution - Norlia Goolamally,; Mazuin Omar,; Azleen Ismail, (2019)
The purpose of this research is to examine the impact of the predictors – quality of service, students perceived satisfaction, and university image on word of mouth (WOM) intention in an open distance learning (ODL) institution. Understanding the expectation of customers is an important component in the marketing kit. Competitive market among educational institution lead educational institutions to think of ways to improve the marketing strategy. The paper also investigates the mediating effect of university image and student perceived satisfaction on WOM intentions of students on the institution. Online survey questionnaires were distributed to 1012 students who are studying at an ODL institution. The sample is selected from the various learning centres and selection is based on the number of semesters these students have been studying at the institution. For the purpose of the research the sample are those who have completed six semesters of study at the institution. The items in the questionnaire were developed using existing constructs. The findings showed that student perceived satisfaction; quality services and university image have a positive and significant impact on word of mouth intention at p 0.05. This study establishes the fact that the quality of services provided, the image of the university and how students feel about the services are predictors of word of mouth intention of students about the university. (Abstract by authors)